Application of Defect Engineering via ALD in Supercapacitors - Tiange Gao; Xiaoyang Xiao; Zhenliang Dong; Xilong Lu; Liwen Mao; Jinzheng Wang; Yiming Liu; Qingmin Hu; Jiaqiang Xu (Batteries)
Supercapacitors are a kind of energy storage device that lie between traditional capacitors and batteries, characterized by high power density, long cycle life, and rapid charging and discharging capabilities. The energy storage mechanism of supercapacitors mainly includes electrical double-layer capacitance and pseudocapacitance. In addition to constructing multi-level pore structures to increase the specific surface area of electrode materials, defect engineering is essential for enhancing electrochemical active sites and achieving additional extrinsic pseudocapacitance. Therefore, developing a simple and efficient method for defect engineering is essential. Atomic layer deposition (ALD) technology enables precise control over thin film thickness at the atomic level through layer-by-layer deposition. This capability allows the intentional introduction of defects, such as vacancies, heteroatom doping, or misalignment, at specific sites within the material. The ALD process can regulate the defects in materials without altering the overall structure, thereby optimizing both the electrochemical and physical properties of the materials. Its self-limiting surface reaction mechanism also ensures that defects and doping sites are introduced uniformly across the material surface. This uniform defect distribution is particularly profitable for high surface area electrodes in supercapacitor applications, as it promotes consistent performance across the entire electrode. This review systematically summarizes the latest advancements in defect engineering via ALD technology in supercapacitors, including the enhancement of conductivity and the increase of active sites in supercapacitor electrode materials through ALD, thereby improving specific capacitance and energy density of the supercapacitor device. Furthermore, we discuss the underlying mechanisms, advantages, and future directions for ALD in this field.